ChemInform Abstract: Iron Halide‐Mediated Regio‐ and Stereoselective Halosulfonylation of Terminal Alkynes with Sulfonylhydrazides: Synthesis of (E)‐β‐Chloro and Bromo Vinylsulfones. Issue 10 (11th March 2014) - Li, Xiaoqing; Shi, Xinhua; Fang, Mingwu; Xu, Xiangsheng
Abstract Halosulfonylation of terminal alkynes is achieved with sulfonylhydrazides as the sulfonyl precursor and iron halide as halide source in the presence of TBHP, allowing the regio‐ and stereoselective generation of (E)‐β‐chloro and bromo vinylsulfones.